A Proteoliposome Method for Assessing Nanotoxicity on Synaptic Fusion and Membrane Integrity. Issue 11 (13th September 2017) - Crowe, Michael; Lai, Ying; Wang, Yongyao; Lu, Jiuwei; Zhao, Minglei; Tian, Zhiqi; Long, Jiangang; Zhang, Peng; Diao, Jiajie
Abstract: Nanoparticles have received significant research interest for potential biomedical applications. Before nanomaterials are administered to patients, their biocompatibility should be thoroughly evaluated through in vitro experiments and other preclinical procedures. Many studies have sought to assess the toxicity of nanomaterials on synaptic transmission for neuroscience applications. However, it may be hard to perform such experiments because of the difficulty associated with delivering synthesized nanomaterials across cell membranes. Here, an in vitro method is demonstrated that mimics neuronal exocytosis, which features protein‐reconstituted liposomes for nanotoxicity testing; the effects of graphene oxide and pristine graphene on fusogenic activity and membrane integrity are examined. These results demonstrate the potential of this system as a novel in vitro platform for assessing the biocompatibility of nanomaterials, drug molecules, and other substances. Abstract : An in vitro vesicle system that mimics neuronal exocytosis is employed for nanotoxicity testing. The experimental scheme consists of leakage and content‐mixing experiments to test the effects of nanomaterials on membrane integrity and synaptic fusion, respectively. Advantages of using proteoliposomes for assessing nanotoxicity on neuronal exocytosis over other techniques like cell‐culture experiments are discussed.